2001
DOI: 10.1016/s0006-3495(01)75966-8
|View full text |Cite
|
Sign up to set email alerts
|

Channel Formation by Salmon and Human Calcitonin in Black Lipid Membranes

Abstract: In this study we investigated the interaction of salmon and human calcitonin (Ct) with artificial lipid bilayer membranes. Both peptides were able to form either transient or permanent channels in the model membranes. The channels formed by salmon Ct at concentration (125 nM) had, on average, a single-channel conductance of 0.58 +/- 0.04 nS in 1M KCl (+10 mV), which is voltage-dependent at lower voltages. Human Ct forms at the same concentration channels with a much lower probability, and high voltages of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Other studies have confirmed those observations [10], and furthermore correlated channel formation with sterol presence in lipid bilayers [11]. Channel assembly induced by other fibrillar proteins, such as Prion [12] and Calcitonin [13] were detected through application of the BLM methodology.…”
Section: Black Lipid Membranessupporting
confidence: 58%
See 1 more Smart Citation
“…Other studies have confirmed those observations [10], and furthermore correlated channel formation with sterol presence in lipid bilayers [11]. Channel assembly induced by other fibrillar proteins, such as Prion [12] and Calcitonin [13] were detected through application of the BLM methodology.…”
Section: Black Lipid Membranessupporting
confidence: 58%
“…Through analysis of linewidths and spectral shifts of the 31 P peak corresponding to the bilayer-forming phospholipids the authors showed that negative potential of the membrane interface is the driving force for the lipid-induced peptide fibrillation. While 31 P NMR generally provided information regarding structural modifications of lipid bilayers upon peptide interactions, 13 C NMR (specifically through application of cross-polarization magic angle spinning, CPMAS) has been a useful tool for elucidating binding and reorganization of the amyloid pep- Fig. (2).…”
Section: Nuclear Magnetic Resonance (Nmr) and Electronic Paramagneticmentioning
confidence: 99%
“…3c). This finding can be related to longer-term receptor activation, as it is the case for sCT, perhaps associated with an increased facility of the CT variants to interact with membrane lipids (42,43). Such an observation could have important repercussions in the use of these reengineered variants as therapeutics.…”
Section: Resultsmentioning
confidence: 94%
“…Although the sequences of these peptides are somewhat dissimilar, all the peptides in this family bind to common G-coupled protein receptors and produce similar effects in many tissues 54,55. Many of the peptides in this family such as human CGRP and calcitonin are also amyloidogenic and aggregate to form membrane-disruptive oligomeric structures 5659. NMR studies on these peptides in detergent micelles have shown that these properties are apparently linked to common structural elements held among the family.…”
Section: Discussionmentioning
confidence: 99%